2023
DOI: 10.1007/s12094-023-03172-y
|View full text |Cite
|
Sign up to set email alerts
|

Anti-PD-1 immunotherapy with dose-adjusted ultra-hypofractionated re-irradiation in patients with locoregionally recurrent head and neck cancer

Abstract: Introduction Patients with recurrent inoperable squamous-cell head-neck cancer (HNSCC) after chemo-radiotherapy have an ominous prognosis. Re-irradiation can be applied with some efficacy and high toxicity rates. Anti-PD-1 immunotherapy is effective in 25% of patients. Immunogenic death produced by large radiotherapy (RT) fractions may enhance immune response. Materials and methods We evaluated the efficacy and tolerance of ultra-hypofractionated immuno-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…For now, there is a lack of clinical studies published in the literature. In a recent study, we showed that re-irradiation of HNC recurrent tumors with 8 Gy fractions together with anti-PD-1 immunotherapy provides high and long-lasting control rates above the expected from chemotherapy or re-irradiation [35].…”
Section: Discussionmentioning
confidence: 96%
“…For now, there is a lack of clinical studies published in the literature. In a recent study, we showed that re-irradiation of HNC recurrent tumors with 8 Gy fractions together with anti-PD-1 immunotherapy provides high and long-lasting control rates above the expected from chemotherapy or re-irradiation [35].…”
Section: Discussionmentioning
confidence: 96%
“…It should also be mentioned that the patients did not require a feeding tube or tracheostomy. Definitive or postoperative hypo-fractionated radiotherapy is considered to be well tolerated and without risks of unacceptable toxicity [66]. Re-irradiation in association with anti-PD-1 immunotherapy is considered an option with benefit in 25% of patients, with activation of the immunogenic cell death mechanism potentiated by hypofractionated radiotherapy.…”
Section: Hypo-fractionation-currently In the Foregroundmentioning
confidence: 99%